Evaluation of Vancomycin Dosing in Intravenous Drug Users Admitted to an Internal Medicine Service. (4th October 2017) - Ferreira, Kristine; Smith, Tonya; Babin, Jennifer; Benefield, Russell
Abstract: Background: Vancomycin clearance can be enhanced in intravenous drug users (IVDUs) with otherwise normal renal function, creating the potential for subtherapeutic exposure with standard dosing schemes. The aim of this project was to describe vancomycin target trough attainment rates in non-critically ill IVDUs. Methods: This was a retrospective chart review of adult IVDUs admitted to the internal medicine service at University of Utah Health from July 1, 2014 to November 30, 2016. Included patients had an estimated creatinine clearance (CrCl) >60 mL/minute (Cockcroft-Gault), and had at least one steady-state vancomycin trough concentration obtained on a consistent dosing regimen. A target vancomycin trough concentration was defined as 15–20 mg/L. Nephrotoxic events were defined as an increase in serum creatinine by 0.5 mg/dL or ≥50% after ≥3 days of therapy. For patients with multiple vancomycin concentrations obtained within a dosing interval, concentrations were fit to a one-compartment open model to estimate pharmacokinetic (PK) parameters. Results: Forty-seven patients were included. The median (IQR) age was 40 years (32–49), and estimated CrCl was 112 ml/minute (90–141 ml/minute). Heroin (89%) and methamphetamine (43%) were the most commonly reported drugs of abuse, and 37 (79%) patients were treated for skin and soft-tissue infections. Forty-five patients (96%) received vancomycin loading doses. The median (IQR) vancomycin loading dose and maintenance regimen was 20.7 mg/kg (19.5–22.4 mg/kg) and 15.2 mg/kg (14.8–17.1 mg/kg) every 12 hours. Forty-four patients (94%) had vancomycin trough concentrations <15 mg/L with their initial regimens. The median (IQR) initial trough concentration was 7.1 mg/L (5.5–10.7 mg/L). No nephrotoxic events were observed. Vancomycin PK parameters were able to be estimated for one patient and are reported in Table 1. Conclusion: Vancomycin trough concentrations were frequently below guideline-based effectiveness targets in this cohort of IVDUs. Additional studies assessing alternative dosing or monitoring schemes for vancomycin in this population are warranted. Disclosures: R. Benefield, Merck: Grant Investigator, Research grant